(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Liquid lipstick is a decorative cosmetic preparation used to add color to the lips. This study aims to determine alternative colorants derived from natural ingredients. The peel of kepok banana flower (Musa paradisiaca L.) which contains anthocyanins can serve as a natural dye, as evidenced by the total anthocyanin content test using the differential pH method, yielding 35.958 mg/L. Three formulations were developed using varying concentrations of kepok banana flower peel extract: F1 (5%), F2 (7.5%), and F3 (10%). The formulations underwent six freeze-thaw (-21°C and 25°C) and cycling (4°C and 40°C) stability cycles, with evaluations of organoleptic properties, viscosity, pH, and spreadability after each cycle. All formulations showed good physical stability which are semi-solid texture, rose scent, homogeneity, brown color, and acceptable spreadability, viscosity, pH, and non-irritant effects. Preference testing with 30 panelists identified F2 as the most favored.